Baseline Characteristics and Latino Versus Non-Latino Contrasts Among Bronx A1C Study Participants. (October 2014) - Walker, Elizabeth A.; Silver, Lynn D.; Chamany, Shadi; Schechter, Clyde B.; Gonzalez, Jeffrey S.; Carrasco, Jeidy; Powell, Danielle; Berger, Diana; Basch, Charles E.
We describe baseline demographic and psychosocial characteristics of low-income, diverse diabetes adults enrolled in a telephonic intervention trial. Environment for the study was New York City (NYC) A1C Registry program. Baseline data were analyzed from 941 participants randomized to either telephonic/print or print-only intervention to improve glycemic control. Summary statistics for key variables were calculated; we highlight baseline contrasts between Latino and non-Latino participants. There were high proportions of Latino (67.7%) and non-Latino Black (28.0%) participants from South Bronx. Mean age was 56.3 years, almost 70.0% were foreign born, and 55.8% preferred Spanish language. Mean A1C was 9.2% and mean body mass index (BMI) 32.1 kg/m 2 . There were significant contrasts between Latino and non-Latino participants for behavioral and psychosocial variables. This telephonic intervention study succeeded in randomizing a large number of low-income, diverse participants with poor diabetes control who are under-represented in studies. Latino versus non-Latino differences at baseline were striking.